(untitled) (Práxis Educativa, 2025)
This paper includes a narrative review and an integrative literature review, aiming to integrate the whole and the parts of a study on the Supervised Curricular Internship in undergraduate Pedagogy programs and the transdisciplinary conception. In the narrative review, it is emphasized that the investigations found connecting the Supervised Internship and transdisciplinarity are very scarce; and in the field of Pedagogy, over 70% of the studies are based on the epistemological foundations presented by Professor Selma Garrido Pimenta. In the integrative review, based on the research question – How does researchers’ understanding of Complexity and Transdisciplinarity affect the Supervised Curricular Internship process? – and following the steps proposed by Botelho, Cunha, and Macedo (2011), the analysis of five studies and the identification of categories are highlighted, revealing characteristics of the relationship between the internship process and transdisciplinarity, in favor of understanding the internship as a transdisciplinary phenomenon. Keywords: Literature review. Supervised Curricular Internship. Transdisciplinarity.